The effect of inflation on economic growth through innovation / Shahiszan Ismail, Nor Azira Ismail and Jamilah Laidin - Ismail, Shahiszan; Ismail, Nor Azira; Laidin, Jamilah (Universiti Teknologi MARA, Kedah, 2022)
Inflation is a term used in economics to indicate the increase in the price of products and services over a given time period, usually a year. One of the effects of inflation is the long periods of uncertainty faced by a country. This global macroeconomic problem, in particular, affects the entire world. The common contributors or causes to inflation are: 1) demand-pull inflation, which is caused by an increase in aggregate demand, and 2) cost-push inflation, which is influenced by a rise in production costs. Other than that, the crisis among countries also could affect world inflation, for example, Russia’s invasion of Ukraine causes rising energy and food prices, in addition to the disruption of agricultural imports and fuel flows which have resulted in the rise in global inflation. In economics, discussions on inflation and economic growth are highly essential as inflation is one of the determinants of economic growth. Thus, this article expands the discussion effect of inflation on economic growth through innovation.